High-Field Diffusion Tensor Imaging of Median, Tibial, and Sural Nerves in Type 2 Diabetes With Morphometric Analysis - Pušnik, Luka; Gabor, Aljoša; Radochová, Barbora; Janáček, Jiří; Saudek, František; Alibegović, Armin; Serša, Igor; Cvetko, Erika; Umek, Nejc; Snoj, Žiga (Journal of neuroimaging, 2025)
BACKGROUND AND PURPOSE: The primary objective was to compare diffusion tensor imaging (DTI) scalar parameters of peripheral nerves between subjects with type 2 diabetes mellitus (T2DM) and those without diabetes. Secondarily, we aimed to correlate DTI scalar parameters with nerve morphometric properties. METHODS: Median, tibial, and sural nerves were harvested from 34 male cadavers (17 T2DM, 17 nondiabetic). Each nerve was divided into three segments. The initial segment was scanned using 9.4 Tesla MRI system (three-dimensional pulsed-gradient spin-echo sequence). DTI scalars were calculated from region-average diffusion-weighted signals. Second segment was optically cleared, acquired with optical projection tomography (OPT), and analyzed for morphometrical properties. Toluidine-stained sections were prepared from last segment, and axon- and myelin-related properties were evaluated. RESULTS: DTI scalar parameters of median and tibial nerves were comparable between the groups, while sural nerves of T2DM exhibited on average 41% higher mean diffusivity (MD) (p = 0.03), 38% higher radial diffusivity (RD) (p = 0.03), and 27% lower fractional anisotropy (FA) (p = 0.005). Significant differences in toluidine-evaluated parameters of sural nerves were observed between the groups, with a positive correlation between FA with fiber density (p = 0.0001) and with myelin proportion (p < 0.0001) and an inverse correlation between RD and myelin proportion (p = 0.003). OPT-measured morphometric properties did not correlate with DTI scalar parameters. CONCLUSIONS: High-field DTI shows promise as an imaging technique for detecting axonal and myelin-related changes in small sural nerves ex vivo. The reduced fiber density and decreased myelin content, which can be observed in T2DM, likely contribute to observed FA reduction and increased MD/RD.
Keywords: senioři; microscopy; diabetické neuropatie; Reproducibility of Results; Anisotropy; mrtvola; reprodukovatelnost výsledků; Cadaver; Sural Nerve; Middle Aged; Sensitivity and Specificity; mužské pohlaví; Diabetes Mellitus, Type 2; Diffusion Tensor Imaging; Diabetic Neuropathies; histology; Adult; magnetic resonance imaging; diabetes mellitus 2. typu; anizotropie; diffusion tensor; Tibial Nerve; Humans; Median Nerve; optical projection tomography; nervus medianus; zobrazování difuzních tenzorů; fractional anisotropy; lidé středního věku; senzitivita a specificita; dospělí; nervus tibialis; Aged; nervus suralis; lidé; Male